PERAN GURU PAI DALAM MENGEMBANGKAN KECERDASAN EMOSIONAL (EQ) DAN KECERDASAN SPIRITUAL (SQ) SISWA SMK KOMPUTAMA MAJENANG - Solehudin, Much (IAIIG Cilacap, 2018)
The purpose of this research is to know the role of PAI teacher in developing the emotional intelligence (EQ) and spiritual intelligence (SQ) of SMK Komputama Majenang students and to know the factors that can influence the emotional intelligence (EQ) and spiritual intelligence (SQ) SMK Komputama Majenang students. Given the many parental roles that are inadequate in facing the current globalization that brings a negative impact on the world of education, caused by lack of knowledge of parents to technological developments. The results of this study indicate that the role of PAI teachers in developing the emotional and spiritual intelligence of students in SMK Komputama Majenang is as a program maker,program implementer, and as an example or role model. The form of attention of a teacher to students in the form of guidance, direction, advice, motivation to learn and programs that can improve students' emotional and spiritual intelligence.